Effects of transcutaneous auricular vagus nerve stimulation on sepsis-induced coagulopathy: protocol for a randomised controlled trial - Chun Yang; Ke Xu; Feng Li; Yingying Zhang; Zhengliang Ma; Mingzhu Yin; Jixiang Zhu; Kun Ni; Quanye Li (BMJ Open)
Introduction Sepsis-induced coagulopathy (SIC) is an early-stage coagulation disorder associated with increased morbidity and mortality in sepsis. It reflects a dysregulated host response and is considered a precursor to disseminated intravascular coagulation and multi-organ failure. Currently, there is no specific treatment for SIC beyond supportive care. Transcutaneous auricular vagus nerve stimulation (taVNS) is a non-invasive neuromodulation technique that has shown potential in regulating inflammation and coagulation pathways. This study aims to evaluate the efficacy and safety of taVNS in improving coagulation dysfunction in patients with SIC, with the primary outcome being the proportion of patients achieving a ≥2-point improvement in SIC score by day 7.Methods and analysis This is a single-centre, randomised, sham-controlled, single-blind clinical trial designed to evaluate the efficacy of taVNS in patients with SIC. This study will enrol 184 adult patients who meet the diagnostic criteria for SIC. Participants will be randomly assigned in a 1:1 ratio to receive either active taVNS or sham stimulation for 7 consecutive days. The intervention will be applied twice daily for 7 consecutive days using standardised stimulation parameters (25 Hz, 3 mA, 60 min/session). The primary outcome is the proportion of patients achieving an improvement of ≥2 points in SIC score from baseline to day 7. Secondary outcomes include platelet count, international normalised ratio, activated partial thromboplastin time, D-dimer, fibrinogen, procalcitonin, C-reactive protein, interleukin-6, angiopoietin-2, systemic immune-inflammation index, lactic acid, duration of antibiotic therapy, length of hospital stay and 28-day all-cause mortality. Adverse events and protocol adherence will also be recorded. Data will be analysed using intention-to-treat principles. Between-group comparisons for the primary outcome will be performed using X2 tests. Repeated measures analysis of variance will be used for longitudinal secondary outcomes.Ethics and dissemination The study protocol has been approved by the Ethics Committee of Yancheng Third People’s Hospital (approval No. 2023-058-01). The trial has been registered in the Chinese Clinical Trial Registry (ChiCTR2400082378). Findings will be disseminated through peer-reviewed publications and academic conferences.Trial registration number ChiCTR2400082378.